LIVING QURAN LAGU KEBANGSAAN INDONESIA RAYA - Minannur, Syamsuri dan (Al-Munir: Jurnal Studi Ilmu Al-Qur'an dan Tafsir, 2022)
The national anthem Indonesia Raya, created by Wage Rudolf Supratman, appeared to encourage the struggle for the independence of the Republik Indonesia. Religious zeal accompanied the ideology of nationality to release the archipelago from the grasp of colonialism. The spirit of the warriors imprinted from the holy book of the Koran, really became a shield of power derived from the Creator. The Quran is the preserved holy book of the Almighty, thus being the only source of information and theological inspiration for freedom. Because the ideology of social liberation has been closed by the invaders. The Living Quran is one of the contemporary research methods that requires strengthening in order to be increasingly recognized for its existence as one of the scientific work processes in the field of Quranic Science. This method is rooted in the phenomenology that makes social phenomena the object of study. Along with its increasingly massive development, normative values in the study of interpretation need to be maintained so that the results of their research remain in line with the function of the Quran as a lifeline. The results showed that the lyrics of the national anthem Indonesia Raya, have content derived from verses of the Quran. The incarnation of the spirit of the archipelago in the form of oceans and land, is depicted in the Quran so that the Indonesian people have the power to realize natural management for mutual prosperity. The stories of the prophets and apostles contained in the Quran became a form of social ideology that became the glue of nationality.